Giant carotid chemodectoma treated with a combination of surgery and CyberKnife radiotherapy: a case report and review of the literature - López Arcas, José M.; Colmenero, César M.; Martínez, Roberto; Martin Hernan, Fatima; Ruiz Sánchez, Beatriz; Aragoneses, Juan Manuel (My University, 2022)
Background: Paragangliomas are rare vascular neuroendocrine tumors that develop in the extra-adrenal paragan¿ glion tissue. They occur most commonly at the carotid bifurcation, where they are known as carotid body tumors. Most paragangliomas are benign, locally aggressive, infltrative tumors. Approximately 10% of patients with para¿ gangliomas develop distant metastases, 10% present with multiple or bilateral tumors (mostly carotid body tumors), and 10% have a family history of paragangliomas. The malignant transformation of carotid body tumors has been reported in 6% of cases. Case presentation: We present the case of a 64 year-old Caucasian woman with a gigantic glomic tumor mass in the neck. Twenty years before the consultation, the patient had undergone an unsuccessful attempt to remove the mass. Over the last 3 years, the patient had felt enlargement of the mass at an increased rate, almost doubling the prior size. Angio magnetic resonance imaging showed a 9 cm paratracheal mass on the left cervical side that laterally displaced the sternocleidomastoid muscle and 2 c m of the trachea. Due to the change in the tumor behavior, the maxillofacial team at Ruber International Hospital decided to remove the tumor surgically after embolization. During the surgery the tumor was gently dissected from the carotid an removed from the carotid bifurcation uneventfully. Two small nodes adhering tightly to the internal carotid adventitia and the posterior torn hole were left in place to avoid any potentially life-threatening complications. The fnal biopsy confrmed the initial diagnosis of carotid body paraganglioma and showed a Ki-67 expression of 19%. Due to the aggressive growth behavior and high Ki-67 expres¿ sion of the tumor, the patient was referred to the CyberKnife Unit of Ruber International Hospital for treatment of the remaining nodes. Conclusions: The management of cervical paragangliomas is difcult and remains a challenge. Although the likeli¿ hood of tumor control is high with surgical or radiotherapeutic treatments, we currently lack consensus regarding the best treatment option. Nevertheless, in selected complex cases, such as the case we present, the combination of surgery and radiosurgery may allow complete local tumor control with minimal morbidity. Keywords: Chemodectoma, Carotid sheath tumors, Radiotherapy, CyberKnife